Management of anthracnose of soybean caused by Colletotrichum truncatum - S.L. KALE, B.G. BARHATE* and (Indian Phytopathology, 2016)
A study was conducted in the Department of Plant Pathology and Agricultural Microbiology, MPKV, Rahuri, Ahemednagar, Maharashtra during 2014 to 2015 to control Colletotrichum truncatum causing anthracnose or pod blight of soybean with fungicides and bioagents. All the fungicides and bioagents evaluated in vitro were found effective against C. truncatum and recorded significant inhibition of the test pathogen over untreated control. However, carbendazim was found most effective and recorded 0.66mm mean colony diameter and significantly highest growth inhibition (99.26%) of the test pathogen. This was followed by mancozeb (98.88%), hexaconazole (84.44%), chlorothalonil (80.00%), propiconazole (78.15%)and difenconazole (32.22%). Out of the six bioagents evaluated in vitroT. virideandT.harzianum recorded significantly highest growth inhibition (78.88%) followed by T. hamatum (77.04%), yeast (40.37%), P. fluorescens(27.77%) and mehandi leaf extract (17.77%). In vitro physiological study of pathogen shows that C.truncatum grew well at 27Â°C temperature with 75% relative humidity.